KONSEP PENGENALAN MATEMATIKA PERMULAAN DI SENTRA NUMERASI TK B LABSCHOOL JAKARTA - Sherlita Maya Agustin; Kristiana Maryani; Dian Surya Aprillyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to describe the concept of early mathematics introduction in the Numeracy Center at TK B Labschool Jakarta, including the learning concept, numeracy learning planning, and the use of learning media and educational play materials. This study employed a qualitative descriptive case study approach. The research participant was the numeracy center teacher at TK B Labschool Jakarta. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman interactive model, which consists of data reduction, data display, and conclusion drawing. Data validity was ensured through prolonged observation, persistent diligence, technique triangulation, and peer discussion. The findings revealed that the implementation of early mathematics learning at the Numeracy Center has been carried out in accordance with the characteristics of early childhood education through meaningful play activities and the use of concrete learning materials. Learning plans were developed based on initial diagnostic assessments, weekly teaching modules, and children's developmental needs. The learning process focused not only on number recognition and counting skills but also on classification, patterning, measurement, comparison, and recognition of simple geometric shapes. Teachers acted as facilitators by providing guidance, stimulation, and reflection throughout the learning process. The use of various learning media and educational play materials enhanced children's engagement, making early mathematics learning more active, enjoyable, and meaningful